Language usage in some traditional rituals in Northern Sotho - Mankga, Ramasela Wilhemina (University of Limpopo (Turfloop Campus), 2013)
Most people feel scared and ashamed when practising their rituals and using the relevant language. The aim of this study is to be an eye opener to make people to change their behaviour and attitude. They should be free to perform their rituals with pride and dignity and regard them as valuable. Qualitative method was used to gather the information and data in this research in which interviews were conducted. Males and females were visited at their homes from villages around Mamehlabe, Ngwanallela, gaSebotse, gaMashashane and only few were quoted. Their responses were transparent in a way that it is clear that the Northern Sotho people have their own way of using language and performing rituals. It is recommended that in the performance of rituals and language usage, a full explanation is needed to accumulate practical implementation. The society at large need to be educated in order to transfer the information to the younger generation.
Thesis (M.A.) --University of Limpopo, 2013
Keywords: Rituals; Culture; Birth rituals; Initiation; 418.8; Language and languages; Sociolinguistics